PENERAPAN STANDARD OPERATING PROCEDURE DAN REBRANDING PADA SPARKLING EXPRESS LAUNDRY - Cindy Fransiska; Candy Candy (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Digital marketing is a form of direct marketing that will connect sellers with consumers using interactive technologies such as social media, email, websites, etc. One of the digital marketing strategies that can implement business image rebranding. Apart from implementing rebranding, a business also requires a Standard Operating Procedure (SOP). The results of the output of this practical work have a very significant impact which is to increase profit compared to before the implementation of the output and minimize errors that occur in the scope of work.